Best friend next door - Mackler, Carolyn (Scholastic Press, 2015)
In the summer before fifth grade, Hannah is facing some emotional upheavals--her best friend from next door just moved away and her dad and stepmom are expecting a baby. When Emme moves next door, Hannah starts out determined not to like her, but as the girls discover how much they have in common and develop an appreciation for their differences, they gradually become good friends.